Synthesis, Characterization and Biological Activity of Some New Pyrimidine Derivatives - Abdul-Bary, Mariam; Haddad, Batool; Al Ameri, Jenan (Journal of Multidisciplinary Applied Natural Science, 2025)
In this study, four derivatives of pyrimidine-2(1H)-thione were synthesized via the reaction between the compounds of α,β-unsaturated ketone and thiourea. The first step included a reaction between 1 mol of four different derivatives of primary amines and 1 mol of benzil. In the second step, the resulting compound was interacted with acetone to prepare α,β-unsaturated ketone. In the third step, the resulting compound was then interacted with thiourea to form the following compounds: 5,6-dihydropyrimidin-2(1H)-thione. The IR, (1H and 13C) NMR and MS spectroscopies were used to confirm the structures of the prepared compounds and examine their antibacterial activities against (Staphylococcus aureus and Escherichia coli) by well diffusion method. It was found that the synthesized compounds have high activity against these two types of bacteria, especially compound P2 had the most inhibitory activity.